PENGALAMAN KELUARGA DALAM PERAWATAN ANAK SPEECH DELAY DI WILAYAH KERJA PUSKESMAS TERJUN - Nova Linda Rambe; Wellina BR. Sebayang; Debora Lestari Simamora; Amelia Syafitri (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2026)
Speech delay in children is a developmental disorder frequently found in the service area of Terjun Community Health Center. This study aimed to explore children's nutritional intake, sources of information, family management practices, and factors contributing to speech delay in children in this area. This study employed a qualitative method using a phenomenological approach with a snowball sampling technique. Data were collected through in-depth interviews with 5 families who had children with speech delay. The findings indicated that children's diets were relatively limited and lacked nutritional variety, consisting mainly of rice, vegetables, fish, eggs, and several fruits such as bananas and papaya. Most mothers provided formula milk from infancy due to difficulties in breastfeeding, which may influence children’s speech development. The inconsistent administration of supplements such as Cerebrovit, vitamin C, herbal honey, and fish oil may reduce their potential effectiveness. Parental experience also played an important role in recognizing speech delay, as parents compared their child’s speech development with that of older siblings. Family management strategies included intensive interaction and speech stimulation, and some families sought professional assistance for speech therapy. Genetic predisposition was also identified as a contributing factor. In addition, inadequate maternal nutritional intake during pregnancy due to economic constraints was reported to contribute to speech delay in children. In conclusion, speech delay among children in the Terjun Community Health Center area is associated with multiple factors, including limited dietary intake, inconsistent supplement administration, parental experience in recognizing developmental delays, genetic predisposition, and inadequate maternal nutrition during pregnancy.